The age of revolutions in global context, c. 1760-1840 - Armitage, David, 1965-; Subrahmanyam, Sanjay (Palgrave Macmillan, 2010)
"Distinguished historians provide uniquely broad coverage of the dynamics of global and regional change in the late eighteenth and nineteenth centuries. Sheds new light on the American, French and Haitian revolutions, alongside ground-breaking treatments of Africa's place in world history and Asia's age of revolutions"--Provided by publisher.